Exploring Simple Addictive Weighting (SAW) for Decision-Making - Khoiry, I'tishom Al; Amelia, Dhea Rizky (Jurnal Inovtek Polbeng Seri Informatika, 2023)
TheÂ Simple Additive Weighting (SAW) method is a well-known and widely utilized approach for decision-making in various disciplines. The SAW method involves a step-by-step process that enables decision-makers to evaluate and rank alternatives based on their respective attribute values and assigned weights. Within this context, this paper aims to provide a comprehensive exploration of SAW for decision-making. This study demonstrates the utilization of the SAW method in supplier selection, which aims to streamline and optimize the supply chain management process for organizational business.The resultsderived from the study have revealed its practicality, effectiveness, and adaptability in handling multi-criteria decision problems, by examining its principles, advantages, limitations, and application based on real situations. It's important to note that the method's reliance on accurate weight assignment to criteria poses a challenge. This process can be subjective and intricate, especially when faced with conflicting objectives. However, SAW stands as a valuable addition to the decision-maker's toolkit, providing a structured and transparent framework for making well-informed choices amidst complexity.